2020
DOI: 10.1590/0037-8682-0562-2019
|View full text |Cite
|
Sign up to set email alerts
|

The use of the circulating cathodic antigen (CCA) urine cassette assay for the diagnosis and assessment of cure of Schistosoma mansoni infections in an endemic area of the Amazon region

Abstract: Introduction: Schistosomiasis is a poverty-related disease that affects people in 78 countries worldwide. This study aimed to evaluate the point-of-care circulating cathodic antigen (POC-CCA) test performance using sensitive parasitological methods as a reference standard (RS) in individuals before and after treatment. Methods: The RS was established by combining the results of 16 Kato-Katz slides and the Helmintex ® method. Positivity rates of the POC-CCA test and Kato-Katz and Helmintex ® methods were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The lower CR using the POC-CCA test as compared to the CR measured by KK (p<0.001) implies that PZQ is not as efficacious as it was thought before. The present PZQ CR using POC-CCA is similar to previous reports [ 25 , 26 ] but higher than the findings of other studies [ 24 , 44 , 49 ]. The previous studies measured CRs six weeks and above after treatment, possibly leading to re-infections and thereby contributing to the lower CR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The lower CR using the POC-CCA test as compared to the CR measured by KK (p<0.001) implies that PZQ is not as efficacious as it was thought before. The present PZQ CR using POC-CCA is similar to previous reports [ 25 , 26 ] but higher than the findings of other studies [ 24 , 44 , 49 ]. The previous studies measured CRs six weeks and above after treatment, possibly leading to re-infections and thereby contributing to the lower CR.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the KK method that is being used for the assessment of PZQ efficacy is not sensitive enough for detecting light infections [ 17 , 24 , 25 ], and as a result, overestimation of CR is highly likely. In light of this fact, WHO suggested the use of urine point of care circulating cathodic antigen (POC-CCA) test along with KK in endemic countries for monitoring and evaluation of SCH control programs [ 26 ]. Circulating cathodic antigen (CCA) is one of the major schistosomal gut-associated glycoproteins regurgitated by the live adult parasites, and majority is secreted in urine.…”
Section: Introductionmentioning
confidence: 99%
“…These POC-ECO quality assurance and quality control issues reinforce previous concerns with Schisto POC-CCA ® from Rapid Medical Diagnostics (POC-CCA) both in freshly-collected 4,26 and stored urine 3,5 . Moreover, results from earlier studies based on a discontinued version of POC-CCA requiring one drop of urine and one drop of buffer [16][17][18][27][28][29][30][31][32] may not be comparable with those based on the new version of POC-CCA requiring two drops of urine and no buffer 3,4,24,33-35 .…”
Section: Discussionmentioning
confidence: 89%
“…The sediment was then spread over slides of filter papers for examination by optical microscopy. Although laborious and time-consuming, HTX significantly increases egg detection in stool samples from low-intensity transmission areas compared with routine KK [15][16][17][18] .…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…For S mansoni , the circulating cathodic antigen urine cassette assay version 1 (CCA1) test was investigated in 24 studies, reported in 23 articles with Kato-Katz technique as the reference test, 23 , 33 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 totalling 36 comparisons against single (one comparison), duplicate (17 comparisons), quadruple (ten comparisons), sextuple (seven comparisons), or 16 Kato-Katz thick smears (one comparison). Prevalence ranged from 5·5% to 94·7% and the point estimates ranged from 36% to 99% for sensitivity and from 19% to 93% for specificity across all of the CCA1 test comparisons ( appendix 1 pp 19–20 ; appendix 2 p 10–15 ).…”
Section: Resultsmentioning
confidence: 99%